DNA methylation in the pathogenesis of type 2 diabetes in humans - Cajsa Davegårdh; Sonia García-Calzón; Karl Bacos; Charlotte Ling (Elsevier, 2018)
Background: Type 2 diabetes (T2D) is a multifactorial, polygenic disease caused by impaired insulin secretion and insulin resistance. Genome-wide association studies (GWAS) were expected to resolve a large part of the genetic component of diabetes; yet, the single nucleotide polymorphisms identified by GWAS explain less than 20% of the estimated heritability for T2D. There was subsequently a need to look elsewhere to find disease-causing factors. Mechanisms mediating the interaction between environmental factors and the genome, such as epigenetics, may be of particular importance in the pathogenesis of T2D. Scope of Review: This review summarizes knowledge of the impact of epigenetics on the pathogenesis of T2D in humans. In particular, the review will focus on alterations in DNA methylation in four human tissues of importance for the disease; pancreatic islets, skeletal muscle, adipose tissue, and the liver. Case-control studies and studies examining the impact of non-genetic and genetic risk factors on DNA methylation in humans will be considered. These studies identified epigenetic changes in tissues from subjects with T2D versus non-diabetic controls. They also demonstrate that non-genetic factors associated with T2D such as age, obesity, energy rich diets, physical activity and the intrauterine environment impact the epigenome in humans. Additionally, interactions between genetics and epigenetics seem to influence the pathogenesis of T2D. Conclusions: Overall, previous studies by our group and others support a key role for epigenetics in the growing incidence of T2D. Keywords: Epigenetics, DNA methylation, Type 2 diabetes